2016
DOI: 10.1371/journal.pone.0149068
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Enhancement of Lateral Inhibitory Circuit Maintains Cross Modal Cortical Reorganization

Abstract: Deprivation of one modality can lead to the improvement of other intact modalities. We have previously reported that visual deprivation drives AMPA receptors into synapses from layer4 to 2/3 in the barrel cortex and sharpens functional whisker-barrel map at layer2/3 2 days after the beginning of visual deprivation. Enhanced excitatory synaptic transmission at layer4-2/3 synapses is transient and returns to the base line level a week after the beginning of visual deprivation. Here we found that sharpened whiske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Several other functional-anatomical factors than morphological alterations on supragranular pyramidal neurons might additionally contribute to the above described developmental scenario during adolescence. These include changes in local inhibitory circuitry (e.g., increased lateral inhibition: Petrus et al, 2015; Nakajima et al, 2016) and thalamocortical circuitry (e.g., strengthened thalamocortical transmission: Yu et al, 2012; Petrus et al, 2014) as well as effects on other excitatory cell types (i.e., granular and subgranular pyramidal and non-pyramidal spiny neurons). On these cells, for example, spine density was found to be either unchanged (apical dendrites of layer V pyramidal neurons in A1 of early blind mice: Heumann and Rabinowicz, 1982; basal dendrites of subgranular pyramidal neurons in S1 of transiently whisker-trimmed P60 and P90 mice: Briner et al, 2010; Chen et al, 2015; apical and basal dendrites of subgranular pyramidal neurons in A1 and FAES of early deaf cats: Clemo et al, 2016, 2017) or reduced (apical dendrites of layer V pyramidal neurons in V1 of early blind mice: Valverde, 1968; Heumann and Rabinowicz, 1982; spiny non-pyramidal neurons in A1 of early deaf cats: Clemo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other functional-anatomical factors than morphological alterations on supragranular pyramidal neurons might additionally contribute to the above described developmental scenario during adolescence. These include changes in local inhibitory circuitry (e.g., increased lateral inhibition: Petrus et al, 2015; Nakajima et al, 2016) and thalamocortical circuitry (e.g., strengthened thalamocortical transmission: Yu et al, 2012; Petrus et al, 2014) as well as effects on other excitatory cell types (i.e., granular and subgranular pyramidal and non-pyramidal spiny neurons). On these cells, for example, spine density was found to be either unchanged (apical dendrites of layer V pyramidal neurons in A1 of early blind mice: Heumann and Rabinowicz, 1982; basal dendrites of subgranular pyramidal neurons in S1 of transiently whisker-trimmed P60 and P90 mice: Briner et al, 2010; Chen et al, 2015; apical and basal dendrites of subgranular pyramidal neurons in A1 and FAES of early deaf cats: Clemo et al, 2016, 2017) or reduced (apical dendrites of layer V pyramidal neurons in V1 of early blind mice: Valverde, 1968; Heumann and Rabinowicz, 1982; spiny non-pyramidal neurons in A1 of early deaf cats: Clemo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, the enhanced crossmodal activity and functional connectivity in adults (as well as in young individuals) with early sensory loss may be mediated by various forms of synaptic strengthening and remodeling (for review, see Tropea et al, 2009; Lee and Whitt, 2015; Bridi et al, 2018). For example, visual deprivation drives AMPA receptors via extracellular serotonin into synapses of supragranular pyramidal neurons in rat barrel cortex (Jitsuki et al, 2011; Nakajima et al, 2016) and changes the AMPA receptor subunit (GluR1/R2) composition in rat V1 and S1 (Goel et al, 2006), leading to a specific synaptic strengthening in these areas. Likewise, deafening causes a N-Methyl-D-aspartate (NMDA) receptor activation and consequent long-term potentiation at synapses in adult mice V1 (Rodríguez et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have examined the molecular events occurring at synapses during the development of experience-driven neural plasticity. The synaptic recruitment of glutamate AMPA receptors (AMPARs) is a crucial mechanism underlying this process (11,(13)(14)(15)(16)(17)(18)(19)(24)(25)(26)(27). We recently showed that neonatal social isolation disrupts the experience-driven synaptic delivery of AMPARs in the developing rat barrel cortex and results in defective sensory processing and altered behaviors (9,10).…”
mentioning
confidence: 99%
“…At the molecular/cellular level, the VD increases the extracellular serotonin in the barrel cortex and facilitates the synaptic delivery of AMPA-type glutamate receptors (AMPARs) at L4-2/3 synapses in the barrel cortex of juvenile rats [26]. Additionally, transient strengthening of excitatory synapses at L4-2/3 in the barrel cortex could trigger an enhancement of the inhibitory inputs to the neighboring barrel, and sustained lateral inhibition can maintain the sharpening of whisker-barrel map [27]. The functional architecture of the adult neocortex is presumed to be organized by the excitatory-inhibitory balance [28].…”
Section: Discussionmentioning
confidence: 99%